Applying panel data models to estimate road safety in Poland 2001–2012 - Weszczak, Anna Danuta (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This paper presents econometric model for road safety in different regions of Poland in 2001–2012. The study is an attempt to indicate the socio-economic determinants of road safety. On the basic of literature and reports of institutions studied the issue and taking into account the data availability following variables were considered: the expenditure of local governments in Department 600 – Transportation and communication, roads quality, motorization rate, length of road network and share of heavy vehicles in all vehicles. The study was conducted for three different risk indictors: number of fatalities per 1 million inhabitants, number of fatalities per 1 million vehicles and number of fatalities per 100 road accidents. Panel data models – fixed effect model (FEM) and random effects model (REM) were used to estimate parameters of equation.